The Atypical Effective Connectivity of Right Temporoparietal Junction in Autism Spectrum Disorder: A Multi-Site Study - Hao, Zeqi; Shi, Yuyu; Huang, Lina; Sun, Jiawei; Li, Mengting; Gao, Yanyan; Li, Jing; Wang, Qianqian; Zhan, Linlin; Ding, Qingguo; Jia, Xize; Li, Huayun (Frontiers in Neuroscience, 2022)
Social function impairment is the core deficit of autism spectrum disorder (ASD). Although many studies have investigated ASD through a variety of neuroimaging tools, its brain mechanism of social function remains unclear due to its complex and heterogeneous symptoms. The present study aimed to use resting-state functional magnetic imaging (rs-fMRI) data to explore effective connectivity between right temporoparietal junction (RTPJ), one of the key brain regions associated with social impairment of individuals of ASD, and whole brain to further deepen our understanding of the neuropathological mechanism of ASD. This study involved 1454 participants from 23 sites from the Autism Brain Imaging Data Exchange (ABIDE) public dataset, which included 618 individuals with ASD and 836 with typical development (TD). First, a voxel-wise granger causality analysis (GCA) was conducted with the RTPJ selected as the region of interest (ROI) to investigate the differences in effective connectivity between the ASD and TD groups in every site. Next, to obtain further accurate and representative results, an image-based meta-analysis was implemented to further analyze the GCA results of each site. Our results demonstrated that abnormal causal connectivity between the RTPJ and widely distributed brain regions, and associated with social impairment in individuals with ASD. The current study could help to further elucidate the pathological mechanisms of ASD and provides new perspective for future research.